The role of individualist and collectivist orientations on self-determined motivation: integrating self-determination theory and group processes - Rentzelas, Panagiotis (2009)
The main aim of this thesis was to examine the role of individualism and collectivism as situational group norms on intrinsic motivation. A further aim was to examine the effect of individual differences in individualist and collectivist orientations on the effect of autonomous motivation on intention and behaviour. This research integrated the concept of self-determined and intrinsic motivation as postulated in Self-Determination Theory (Deci & Ryan, 1985a, 2000,2002), individualism and collectivism as group norms from a Social Identity Theory perspective (Tajfel 1974,1978; Tajfel & Turner, 1979; McAuliffe et al, 2003), independence and interdependence as individual differences in self-construals from Self-Systems Theory (Markus & Kitayama, 1991b), and constructs from the Theory of Planned Behaviour (Ajzen, 1985). After reviewing the literature in Chapter 1, it was hypothesised that individualist and collectivist group norms could be situationally induced and would interact with the environmental contingencies that that support intrinsic motivation in predicting people's levels of intrinsic motivation. It was also hypothesised that individualist and collectivist orientations at an individual difference level would change the relationship between autonomous motivation and intentional behaviour. Chapter 2 presents the development of a methodological tool to manipulate individualist and collectivist group norms. Two studies employing a minimal group paradigm investigated the effect of individualist or collectivist group norms on evaluation of employees behaviour, group tolerance, relatedness, and identification in group members from individualist (British) or collectivist (Chinese and Greeks) cultural backgrounds. Chapters 3 and 4 tackle the main aim of this thesis and the results of three studies provide evidence that when the group norm is individualist group members experience higher levels of intrinsic motivation when they exercise personal choice over a target activity, whereas when the group norm is collectivist group members experience higher intrinsic motivation when a significant other makes a choice for them or provides personal choice. Chapter 5 brings the level of analysis from the group to the individual. This is achieved in a study investigating the moderating effects of independent (individualist) and interdependent (collectivist) self-construals on the effect of autonomous motivation on intentions and actual physical activity behaviour. In the concluding chapter, Chapter 6, the theoretical and practical implications of the research are discussed and directions for future research provided.